Pengaruh Ukuran Perusahaan, Kepemilikan Manajerial, dan Kinerja Keuangan Pada Manajemen Laba - Riska Astari, Ni Ketut; Suputra, I.D.G Dharma (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
This study aims to determine the effect of firm size, managerial ownership and financial performance on earnings management. This research was conducted at mining companies listed on the Indonesia Stock Exchange in 2013-2017. The number of samples in this study were 20 companies with the number of observations obtained as many as 100 observations using the nonprobability sampling method specifically purposive sampling. Data collection uses non-participant observation methods. The data analysis technique used is multiple linear regression analysis. The results of the study show that the size of the company has no effect on earnings management. Managerial ownership has a negative effect. on earnings management. Financial performance has a positive effect on earnings management. The implication of this research theoretically is supporting agency theory and signal theory while practically this research can provide a positive contribution to all parties, especially companies, management, and the main users of financial statements. Keywords : Earnings management, firm size, managerial ownership, financial performance